2. On the Mineralogy of Pyrochlore from the Ilímaussaq Alkaline Intrusion, South Greenland. - Semenov, E. I.; Sørensen, H.; Katajeva, Z. T. (Meddelelser om Grønland, 1968)
Niobium-bearing minerals such as pyrochlore , igdloite ( = lueshite) and epistolite are of widespread occurrence in the Ilímaussaq Intrusion, South Greenland. Furthermore, rock-forming minerals such as eudialyte and rinkite contain one percent or more of Nb2O5. Pyrochlore occurs mainly in rocks of supposed hydrothermal origin and is associated with analcime, natrolite, polylithionite, sphalerite, and a number of other minerals. Four types of pyrochlore are described: Brown pyrochlore which is associated with analcime in aggregates several centimetres across. ao = 10.39 Å, n = 2.02 ± 0.01, sp. gr. = 4.12. Nb2O5 = 60.85, Ta2O5 = 0.09, TiO2 = 0.69, SiO2 = 2.00, TR2O3 = 13. 03, CaO = 6.30, Na2O = 2.97, U3O8 = 0.35 weight percent, etc. Grey pyrochlore forming irregular areas. ao = 10.35 Å, Nb2O5= 42.06, Ta2O5 = 3.63, TiO2 = 4.09, SiO2 = 14.14, TR2O3 = 6.14, CaO = 9.23, Na2O = 5.34 weight percent, etc. (impure material). White earthy pyrochlore which probably forms pseudomorphs after epistolite. Yellow siliceous pyrochlore associated with analcime and neptunite. ao = 10.39 Å, sp. gr. = 3.69, Nb2O5 = 59,91, Ta2O5 = 0.11 , TiO2 = 2.66, SiO2 = 10.26, TR2O3= 2.45, CaO = 8.31 , Na2O = 7.46, U3O8 = 0.20 weight percent, etc. It has not been possible to decide whether the silica content is due to mechanical admixture or to isomorphic substitution. As long as this problem is not solved the Ilímaussaq pyrochlore should most properly be termed siliceous pyrochlore.